Pro HTML5 Programming: Powerful APIs for Richer Internet Application Development - Lubbers, Peter (Apress, 2012)
HTML5 is brand new. Indeed, it isn’t even finished yet. And if you listen to some ornery pundits, they’ll tell you that HTML5 won’t be ready for ten years or more! Why, then, would anyone think that now’s the time for a book called Pro HTML5 Programming? That’s easy. Because for anyone who’s looking for an extra edge to make your web application stand above the rest, the time for HTML5 is right now. The authors of this book have been working with, developing, and teaching HTML5 technologies for more than two years now and can claim with certainty that adoption of the new standards is accelerating at dizzying speeds. Even over the course of writing this book, we’ve been forced to continually update our browser support matrix and reevaluate our assumptions about what is ready to use.